Machine learning in image steganalysis - Schaathun, Hans Georg (Chichester, West Sussex, England : IEEE Press : Wiley, 2012)
"The only book to look at steganalysis from the perspective of machine learning theory, and to apply the common technique of machine learning to the particular field of steganalysis; ideal for people working in both disciplines"--
Includes bibliographical references (p. [267]-277) and index.
Keywords: Machine learning; Wavelets (Mathematics); Data encryption (Computer science); SCIENCE / Waves & Wave Mechanics